Cananga Flower (Cananga Odorata) Extract Gum's Efficacy In Reducing The Index Of Gingivitis-Causing Plaque Of Teuku Nyak Arif Fatih Bilingual Schools Students - Fachri, Navifa; Fitri, Alia Kamila; Keumalasari, Dewi; Shifani, Nadya; Suhartono, Suhartono; Ismi, Nuzulul; Sari, Widya; Sayuti, Muhammad (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2023)
In 2018, the percentage of Indonesians who have gingivitis was 96.58%. Accumulation of plaque and Porphyromonas gingivalis bacteria cause gingivitis, an inflammation of the gingival tissue. Cananga (Cananga odorata), according to research by Anggraini (2021), has an antibacterial activity against Porphyromonas gingivalis. Gum chewing can boost saliva production and reduce bacterial-produced acid. This study aimed to provide an alternative for gingivitis prevention. In general, the three steps of this research are in vitro test, preclinical test, and clinical test. Using the well diffusion method, the antibacterial potential of the cananga flower extract at concentrations of 2.5%, 5%, 10%, 20%, and 40% was examined. Tetracycline 30 Î¼g was the control (+), while ethanol 96% was the control (-). In preclinical test, Lethal Concentration 50% (LC50) was established using the Brine Shrimp Lethality Test (BSLT) method. The clinical test was done using a pretest and posttest control group design method for a week. According to the study's findings, the average inhibition zones were 9.06 mm, 10.53 mm, 12.2 mm, 13.43 mm, and 14.8 mm at doses of 2.5%, 5%, 10%, 20%, and 40%, respectively. Based on the preclinical test, the product material's LC50 is 850.191 ppm. The clinical test showed a decrease in the plaque index of the treatment group by 0.344375. This study concluded that cananga flower extract have antibacterial activity against Porphyromonas gingivalis and cananga flower extract chewing gum has the potential to be effective in preventing and lowering the plaque index that causes gingivitis.